1998
DOI: 10.1557/proc-537-g6.29
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence Properties of InGaN/AlGaN/GaN Light Emitting Diodes with Quantum Wells

Abstract: Electroluminescence spectra of light-emitting diodes based on InGaN/AlGaN/GaN heterostructures with single and multiple quantum wells (QWs) are analyzed by models of radiative recombination in 2D-structures with band tails. Equations of the model fit spectra quite good in a wide range of currents. Parameters of the fit are discussed and compared for single and multiple QWs. Tunnel effects play a sufficient role in blue LEDs with single QWs at low currents; they can be neglected in LEDs with multiple QWs. A new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…3 (see a method of measurements in [8]). The LEDs with MQWs have wider space charge width than ones with SQWs [2][3][4][5]7]; in both cases the width for green LEDs is wider than for blue ones. This fact corresponds to a low probability of tunnel effects in the LEDs with MQWs.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…3 (see a method of measurements in [8]). The LEDs with MQWs have wider space charge width than ones with SQWs [2][3][4][5]7]; in both cases the width for green LEDs is wider than for blue ones. This fact corresponds to a low probability of tunnel effects in the LEDs with MQWs.…”
Section: Resultsmentioning
confidence: 95%
“…The maximum of this band is moving with the current J and voltage on the active layer U: hω max = eU+∆ (in the range = 2.1-2.3 eV). This band was described as a tunnel radiative recombination [4,5]. There is no tunnel band in blue LEDs with MQWs; in this case the blue line is moving with V.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, the threading dislocations have been identified as non-radiative recombination centers by a study of plan-view transmission electron microscopy along with cathodoluminescence (CL) 2 and found to be a major origin for the high reverse-bias leakage currents in p-n diodes by comparing diodes fabricated on dislocated GaN and LEO (lateral epitaxial overgrowth) GaN. 3 In fact, the study of reverse-bias leakage currents in GaN p-n photodiodes, 4 in InGaN blue LEDs, [5][6][7] and even in metalsemiconductor-metal ultraviolet photodetectors 8 has become an important subject, since it is an effective method for the investigation of defect-related conduction under high electric fields. All these studies have indicated that the reverse-bias leakage current is related to carrier tunneling or hopping through the defect states within the bandgap in the GaN-based materials.…”
Section: Introductionmentioning
confidence: 99%